Multimodal and Covert–Overt Convertible Structural Coloration Transformed by Mechanical Stress. Issue 25 (8th May 2020) - Zhou, Qitao; Park, Jun Gyu; Bae, Juyeol; Ha, Dogyeong; Park, Jungyul; Song, Kyungjun; Kim, Taesung
Abstract: Most materials and devices with structurally switchable color features responsive to external stimuli can actively and flexibly display various colors. However, realizing covert–overt transformation behavior, especially switching between transparent and colored states, is more challenging. A composite laminate of soft poly(dimethylsiloxane) (PDMS) with a rigid SiO2 ‐nanoparticle (NP) structure pattern is developed as a multidimensional structural color platform. Owing to the similarity in the optical properties of PDMS and SiO2 NPs, this device is fully transparent in the normal state. However, as their mechanical strengths differ considerably, upon compressive loading, a buckling‐type instability arises on the surface of the laminate, leading to the generation of 1D or 2D wrinkled patterns in the form of gratings. Finally, an application of the device in which quick response codes are displayed or hidden as covert–overt convertible colored patterns for optical encryption/decryption, showing their remarkable potential for anticounterfeiting applications, is demonstrated. Abstract : Self‐assembled SiO2 ‐nanoparticle patterns encapsulated by poly(dimethylsiloxane) are developed as a novel and simple color platform, which can switch between transparent and colored states by mechanical stresses. Upon compression, wrinkles are generated as gratings, enabling the instant display and hiding of information, such as quick response codes and trademarks, by external stimuli. The color platform has potential for application in anticounterfeiting.